STRATIGRAPHIC ARCHITECTURE OF THE SALENTO COAST FROM CAPO D'OTRANTO TO S.MARIA DI LEUCA (APULIA, SOUTHERN ITALY) - ALFONSO BOSELLINI; FRANCESCA R. BOSELLINI; MARIA LUISA COLALONGO; MARIANO PARENTE; ANTONIO RUSSO; ALESSANDRO VESCOGNI (Rivista Italiana di Paleontologia e Stratigrafia, 1999)
The Cretaceous to Quaternary succession of the Apulia Platform cropping out on the eastern coast of the Salento Peninsula shows a special stratigraphic architecture. Whereas on the platform top, i.e. on the Salento Peninsula proper, the succession is at most a few tens of metres thick and is punctuated by unconformities, on the margin and slope of the platform, along the present-day eastern coast of the peninsula, several carbonate systems are laterally disposed and grafted one upon the other. Three of these systems are clinostratified and include well developed reef tracts of Priabonian, early Chattian and early Messinian age. The geologic conclusion of our study is that, since the Late Cretaceous, the eastern coast of the Salento Peninsula grossly coincided with the margin of the Apulia Platform. This paleogeographic element acted as a foreland horst and registered important geodynamic events related to the growth of the adjacent Hellenide and Apennine thrust belts. During the last 60 m.y., the horst carapace was constantly near sea level and sediments were mainly accommodated and preserved on the deep margin and slope of the platform.